Análisis de deforestación y fragmentación dentro y fuera del parque nacional Yasumí: área Tiputini, provincia de Orellana - Poma Tene, Byron Rodrigo (2019)
This research assessed the deforestation and fragmentation of the native forest between 1986 and 2018 in the eastern part of the province of Orellana, Aguarico canton in the parishes: Tiputini, Nuevo Rocafuerte, Santa María de Huiririma and Captain Augusto Rivadeneira , the study area has an area of 374 481 ha of which 43% corresponds to the Yasuní National Park, an area of global importance due to its high biodiversity.Through the supervised classification of Landsat satellite images, land-use changes were determined using TerrSet's Land Change Model tool, GUIDOS and FRAGSTATS were used to quantify fragmentation in and out of the park. The results show that there is native forest coverage domain in the study area; however, there is greater dynamics of deforestation and fragmentation in the surrounding area. In the protected area, the rate of deforestation was 9.9 ha/year, representing a loss of 317 ha of forest cover, of which 284 ha were converted into anthropic uses in 2018; fragmentation, there is core area loss of 0.64%, increased the number and density of patches (29 and 28.93% respectively), on the other hand, the average patch size decreases by 22.64%.In surrounding area the rate of deforestation was 91.28 ha/year, representing a loss of 2 921 ha of native forest, the biggest changes happened by anthropic uses with 2 412 ha these changes are noticeable on the banks of the Napo and Yasuní rivers; fragmentation results in a loss of 3.30% of core area, increasing islands by 221.39% and edges by 63.21%, in the same way increased the number and density of patches by 121.8 and 123.3% respectively, on the contrary decreases, the average size of the patch by 55.91%. Keywords: Land Change, Protected area, Deforestation, Fragmentation, Yasuni National Park.